Huaxian formula alleviates nickel oxide nanoparticle-induced pulmonary fibrosis via PI3K/AKT signaling - Minmin Tian; Liruohan Feng; Mi Tian; Xiaodong Mu; Shi Bu; Jianfeng Liu; Jingyu Xie; Yujie Xie; Ling Hou; Guanghua Li (Scientific Reports)
Abstract As a progressive fibrotic lung disorder with high mortality, pulmonary fibrosis (PF) suffers from inadequate treatment options. While the traditional Chinese medicine (TCM) formulation Huaxian Formula (HXF) demonstrates multi-target therapeutic potential against PF, the identity of its active components and their mechanistic basis of action require systematic investigation. To elucidate the therapeutic effects and pharmacological mechanisms of HXF in treating PF induced by nickel oxide nanoparticles (nano NiO), utilizing network pharmacology (NP), molecular docking, as well as in vivo and in vitro experiments. A comprehensive analysis of authoritative databases identified 121 active compounds, 202 potential therapeutic targets, and 1664 PF-related genes. Among these, 105 overlapping targets were found between HXF and PF. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses identified the PI3K/AKT signaling pathway as both a pivotal mechanism in PF pathogenesis and a primary target of HXF’s therapeutic effects. Molecular docking studies revealed that the six core compounds (quercetin, luteolin, kaempferol, β-sitosterol, isorhamnetin, and formononetin) of HXF exhibited strong binding affinity to proteins involved in the PI3K/AKT pathway. In the rat and A549 cell model, HXF treatment reduced collagen deposition and downregulated the expression of type I collagen (Col-I). Mechanistically, HXF inhibited the phosphorylation of PI3K and AKT. Collectively, these findings suggested that HXF alleviated PF by modulating the PI3K/AKT signaling pathway, providing valuable insights and methods for the development of TCM for PF.